2022
DOI: 10.3390/ijms23041955
|View full text |Cite
|
Sign up to set email alerts
|

Alpha 1 Antitrypsin Regulates Trophoblast Syncytialization and Inflammatory Factor Expression

Abstract: The serine protease inhibitor alpha1-antitrypsin (A1AT) may possess protective functions of impaired organs in a manner independent of its protease inhibitor activity. A1AT expression has been shown to fluctuate in patients with pregnancy-induced hypertension, which suggests that A1AT may play a role in the syncytialization of villous trophoblasts. A1AT expression was knocked down in primary trophoblasts. RNA was extracted from these cells and subjected to RNA-sequencing analysis to determine the levels of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…On the other hand, ER stress may regulate the invasion of extravillous trophoblast cells and relate to the pathogenesis of HDP 29 . Previous study showed that the ER stress inducers tunicamycin and thapsigargin inhibited trophoblast fusion.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ER stress may regulate the invasion of extravillous trophoblast cells and relate to the pathogenesis of HDP 29 . Previous study showed that the ER stress inducers tunicamycin and thapsigargin inhibited trophoblast fusion.…”
Section: Discussionmentioning
confidence: 99%
“…ESCs cells were transfected with either a non-targeting control, or with SERPINA1 (EHU090971, Sigma-Aldrich), TLR3 (EHU019541, Sigma-Aldrich), or TLR4 siRNA (EHU086621, Sigma-Aldrich) using Lipofectamine RNAiMAX (Thermo Fisher Scientific) ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoreactive bands were detected using an enhanced chemiluminescence kit (Merck Millipore, Burlingame, MA, USA) after incubation with horseradish peroxidase-labeled goat anti-rabbit or anti-mouse IgG (1:5,000; Vector Laboratories, Burlingame, CA, USA). Signals were detected using a C-DiGit Blot Scanner (LI-COR, Lincoln, NE, USA) ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, maternal factors such as obesity, hypertension, and autoimmune diseases increase the risk of developing HDP. Furthermore, the degree of inflammation of maternal blood vessels before pregnancy may contribute to the onset of HDP [ 136 , 137 , 138 ]. In recent years, it has been reported that autophagy is involved in placental hypoxia and that autophagy failure is associated with the onset of PE [ 139 , 140 ].…”
Section: Diseases Involving Placental Dysfunctionmentioning
confidence: 99%